Merancang Pengembangan Madrasah Unggul - Agustini Buchari; Erni Moh. Saleh (Institut Agama Islam Negeri (IAIN) Manado, 2016)
Preparation of human resources that are well-qualified and excellent is both an option and orientation for all types and levels of education. Madrasah as community-based educational institutions (community based education) have responsibility in preparing human resources and superior quality. To be able to continue actively preparing qualified human resources and excellent insight, innovative development of superior madrasah is required; which is developed to achieve excellence in output. To achieve this excellence, the input, the process of education, teachers and education personnels, management, education, and supporting facilities should be directed to support the achievement of this goal. Excellenct madrasas should be designed in accordance with the vision, mission and institutional objectives, and the need analysis of academic and institutional system. This should be done with an adequate understanding of the geographic and cultural context.Keywords: Excellent madrasah, educational development, quality education